Pengaruh Model PjBL untuk Meningkatkan Pemahaman Literasi Siswa Kelas V - Aisyah Khairina; Daniaty; Abdurahman Adisaputera, Elly Prihasti Wuriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of implementing the Project-Based Learning (PjBL) model on improving the literacy comprehension of fifth-grade elementary school students. The background of this study is based on students' low literacy skills in understanding, analyzing, and interpreting reading texts at the elementary school level. The research method used was an experimental method with a pretest-posttest control group design. The study subjects consisted of two classes: an experimental class treated with the PjBL model and a control class treated with conventional learning. The research instrument was a literacy test covering aspects of reading comprehension, critical thinking, and reflective writing skills. Data were analyzed using a t-test to determine significant differences between the two groups. The results showed a significant effect of implementing the PjBL model on improving students' literacy comprehension. Students learning with the PjBL model demonstrated better results in understanding text content, developing ideas, and applying critical thinking skills compared to students learning with conventional learning. Thus, the Project-Based Learning model is effective as an alternative learning strategy to improve elementary school students' literacy.